Assessment of the Impact of Nursing Interruptions on Pharmacist Workflow and Efficiency. Issue 1 (January 2016) - Alhammad, Abdullah M.; Stashek, Chad S.; Churchill, William; Fanikos, John
Background: Interruptions in the pharmacy setting by nurses are common. While the source of nurse-generated interruptions may be variable, the appropriateness of these interruptions remains unknown. Objective: To evaluate the impact and appropriateness of nursing interruptions on pharmacist workflow resulting from telephone calls, alphanumeric pagers, and in-person interactions. Methods: An electronic data collection tool was created to record nursing-based interruptions of pharmacists through telephone calls, pages, and in-person interactions. The data were collected during all pharmacist shifts (day, evening, and night) over 14 days in 2 separate, 7-day data collection periods in December 2011 and January 2012. The data collection form comprised 7 questions that addressed the purpose of this study, including the shift; unit location; type, nature, and appropriateness of the interruption; estimated time spent; and whether the interruption was duplicated. Results: A total of 3, 531 interruptions were documented during the 14 days of data collection; an average of 252 data points per day were recorded by the pharmacists. About 55% of the interruptions were initiated through alphanumeric pagers, 33% from phone calls, and 12% from face-to-face interactions. Sixty-three percent of the total interruptions were annotated as appropriate interruptions, while 37% of were annotated as inappropriate interruptions. The total time spent addressing the interruptions deemed inappropriate was 75 hours during the study period. Conclusion: Distinct opportunities exist for process improvement changes, as well as educational and behavioral changes, that would greatly benefit nursing and pharmacy staff.